2021
DOI: 10.1177/15353702211049149
|View full text |Cite
|
Sign up to set email alerts
|

CCNB1 promotes the development of hepatocellular carcinoma by mediating DNA replication in the cell cycle

Abstract: In our studies, cyclin B1 ( CCNB1) mRNA and protein were overexpressed in hepatocellular carcinoma (HCC) tissues compared with non-HCC tissues. Moreover, CCNB1 was overexpressed in the serum of HCC patients. The expression of CCNB1 was associated with several crucial clinicopathologic characteristics, and the HCC patients with overexpressed CCNB1 had worse overall survival outcomes. In the screening of interactional genes, a total of 266 upregulated co-expression genes, which were positively associated with CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…The presence of a low-grade cancer or the absence of cancer were anticipated in HCC patients [ 39 ]. Another study reported the escalated synthesis of CCNB1′s mRNA and proteins in patients with HCC [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a low-grade cancer or the absence of cancer were anticipated in HCC patients [ 39 ]. Another study reported the escalated synthesis of CCNB1′s mRNA and proteins in patients with HCC [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence suggests that m6A/m1A/m5C regulated genes play important biological roles in the progression of HCC, which can be used to determine the prognosis and survival of HCC patients. The signaling pathways, including the cell cycle, DNA replication, and WNT are closely associated with cancer progression (28)(29)(30)(31)(32)(33)(34). Previous studies have found that ASF1B is highly expressed in HCC, and elevated ASF1B expression level is associated with poor prognosis in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The spindle rotation can be blocked by CDK-1 through the inhibition of the interaction between dynein with LIN-5-ASPM-1 and microtubules at the meiotic spindle poles, while through suppression of the CDK-1, APC could promote the spindle rotation ( 28 ). Due to the participation of CCNB1 in the cell cycle of HCC through the regulation of DNA replication, CCNB1 can be used for the diagnosis of early-stage HCC ( 29 ). Immunohistochemical analysis showed significantly high level of CCNA2 was observed in the tissues from breast cancer patients compared to that from normal controls ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the participation of CCNB1 in the cell cycle of HCC through the regulation of DNA replication, CCNB1 can be used for the diagnosis of early-stage HCC ( 29 ). Immunohistochemical analysis showed significantly high level of CCNA2 was observed in the tissues from breast cancer patients compared to that from normal controls ( 29 ). By regulating the p-ERK1/2/p-SMAD2/Snail pathway, TOP2A could enhanced the process of epithelial–mesenchymal transition and subsequently promote the metastasis of HCC ( 27 ).…”
Section: Discussionmentioning
confidence: 99%